Abordagens de inclusão: o dinamismo de professores diante de alunos com TDAH - Silva, Jordana Alves da (Universidade Federal do Tocantins, 2024)
This research presents pedagogical proposals to help teachers aiming at a practice of inclusion of students who have Attention Deficit Hyperactivity Disorder (ADHD), in order to meet the specific particularities that the disorder is committed to, this is inferred due to the intensity in which the symptoms of ADHD can harm the student's learning, in addition, practices must also be able to guarantee the quality of teaching for other students who do not have special needs. However, the work benefits math teachers from the moment it presents methodologies for teaching the discipline and proposes some examples of activities to work with students who have ADHD. Therefore, this research is structured in character of bibliographical methodology with study in research already developed by other authors, portraying a descriptive characteristic, in which it provides surveys of information and with a qualitative approach in order to understand the research object